Determinação da capacidade portante de pilares de concreto armado pelo Método da Coluna-Modelo - Polillo, Vera Regina (1983)
This thesis presents a computer program for the determination of the load-bearing capacity of reinforced concrete columns according to the CEB-FIP's model column method. This program employs two incremental-iterative procedures: a load controlled procedure and a curvature controlled one. The second procedure is used when the convergence of the first one becomes slow and also in the determination of the descending branch of the load-displacement curve. Both the influence of the displacements on the equilibrium of the column and the non-linear stress-strain relations for the materials are considered in the analysis. The reduced modulus method is used to account for the creep effects. The computer program is directly applicable to an isostatic column subjected to a constant axial force along its length, whose cross-section (concrete and reinforcement) is constant and symmetrical with respect to the plane of the loads and whose deflection curve doesn't have an inflection point and is tangent to the vertical line in the most heavily stressed section. This program can be used to determine the loadbearing capacity for a given column under the action of either short, long or long-short-time loading. It gives the values of the load-bearing capacity according to both the model column method and the improved model column method. Some illustrative examples and some tables giving the first order moment capacities are presented.